Effect of a Ten-Week Short Message Service-Based Intervention on Self-Management of Type-2 Diabetes Patients in Bali, Indonesia - Damayanti, Made Rini; Antari, Gusti Ayu Ary; Nopriani, Ni Luh Putu (Nurse Media Journal of Nursing, 2021)
Background: Diabetes mellitus is a chronic disease that may pose serious complications if poorly managed. The application of mobile technology (m-health) ranging from simple to more complex programs in diabetes management has the potential to foster patients’ active involvement in their care. However, the evidence of m-health effectiveness on the self-management of type-2 diabetes patients in low- and middle-income countries is still mixed.Purpose: To evaluate the effect of a ten-week short message system (SMS)-based intervention (Tweek SMSDM) on self-management of type-2 diabetes patients.Methods: A quasi-experimental study was performed in two groups. The intervention group (n=30) received additional daily automated messages to enhance their diabetic self-care practice, while the control group (n=30) continued to follow the standard program only. Pre- and post-intervention data were measured in both groups using the Indonesian version of the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. T-test, Mann-Whitney, Wilcoxon Signed-Ranks, McNemar and Fisher exact tests were carried out to analyze the data.Results: After ten weeks, the intervention group showed significant mean changes in the domains of general diet (0.42±1.08; p=0.034), specific diet (1.75±1.42; p=0.0001), exercise (1.02±1.85; p=0.005), blood-glucose testing (0.53±1.67; p=0.009), and foot care (4.75±2.51; p=0.001) before and after the intervention, while the control group did not. This study also found significant differences in the mean scores for each domain of the SDSCA between the intervention and the control groups (p<0.05).Conclusion: The Tweek SMSDM program can improve the self-management of type-2 diabetes patients and positively affect each domain in the SDSCA. The findings of this study recommend that nurses integrate the program into patient treatment regimes in primary healthcare centers; therefore, patients and their significant others can play more proactive roles in their diabetic care.